Transdermal delivery of water‐soluble fluorescent antibody mediated by fractional Er:YAG laser for the diagnosis of lupus erythematosus in mice. Issue 3 (28th December 2018) - Zhang, Xiaoming; Jiang, Honghao; Zhang, Yamin; Ren, Guichao; Dong, Liyun; Zhu, Jintao; Tu, Yating; Tao, Juan; Yang, Liu
Abstract : Objectives: Although transdermal drug delivery system (TDDS) has been successfully used for delivering small molecules, its application in the delivery of diagnostic antibodies has been limited due to their large size. In this study, we aim to obtain a broad insight in the dynamics of TRITC‐conjugated Goat Anti‐Mouse IgG (T‐IgG) uptake in fractional Er:YAG laser pretreated skin and provide a new technical option for detecting lupus erythematosus (LE) in mice. Methods: The skins of SD and MRL/lpr mice were treated by fractional Er:YAG laser followed by external application of T‐IgG. The classic Franz diffusion method was used to observe the effects of different fractional fluences, densities and antibody concentrations on transdermal delivery of T‐IgG at different time points (2, 4, 6, 8, 20, and 24 hours). Frozen tissue sections and confocal microscopy were used to observe the distribution of T‐IgG on the sagittal and coronal planes of murine skin. Results: Increased laser fluence (12.5 J/cm 2 to 37.5 J/cm 2 ) within 24 hours resulted in the obvious increase in transdermal amounts of T‐IgG during the early stage (before 8 hours). However, increasing laser density (100 pores/cm 2 to 200 pores/cm 2 ) produced a significant increase in T‐IgG permeation during the late stage (20 and 24 hours). Unlike fluence and density, increase in T‐IgG loading concentration (0.5 to 2 μg/μl) led to continuous increase in the whole process of transdermal delivery. T‐IgG appeared in the micro‐pores of SD mice skin within 4 hours after treatment in vivo . After 24 hours, it was observed in the skin. In MRL/lpr mice, positive lupus band testing (LBT) could be found on the skin lesion after laser and T‐IgG external application. Conclusions: Fractional Er:YAG laser can help antibodies (150 kDa) to implement effective and controllable transdermal delivery. LBT can be achieved in MRL/lpr mice using TDDS in vivo, which may contribute to the minimally invasive diagnosis of LE. Lasers Surg. Med. 51:268–277, 2019. © 2018 Wiley Periodicals, Inc.